Psychological safety perception in community pharmacies: A randomized controlled trial of agile interventions - Dragana Jocic (Elsevier, 2024)
Background: Agile coaching, recognized as a more advanced methodology compared to education, is hypothesized to yield superior outcomes in enhancing psychological safety perception. Objective: Investigating the effectiveness of agile interventions versus no intervention on psychological safety perception, this randomized controlled trial aimed to clarify outcomes. Methods: The survey sample consisted of 54 licensed pharmacists, with each group comprising 18 participants: E1 underwent Agile Coaching, E2 underwent Agile Education, and C served as the control. After six weeks, psychological safety perception was measured using a validated scale, and statistical analyses, including the Kruskal-Wallis test and Mann-Whitney U test, were conducted. Results: The group undergoing agile coaching showed the most substantial enhancements in psychological safety perception compared to others. Mann-Whitney U test revealed no significant difference in psychological safety perception between E1 and E2 groups before (Z = −0.938, p = 0.348) and after intervention (Z = −1.269, p = 0.204). Significant differences were observed between E1 and C both before (Z = −2.693, p = 0.007) and after intervention (Z = −1.414, p = 0.157). Significant differences were found between E2 and C before (p = 0.038) but not after intervention (p = 0.962). Conclusions: The findings suggest that agile coaching could be an effective intervention for enhancing psychological safety in organizational settings, particularly in community pharmacies. Further research is warranted to explore long-term effects and generalize findings to broader contexts.